The Dynamics of the Epidemiological Situation of Tick Borne Encephalitis in the Far East - G. N. Leonova (Эпидемиология и вакцинопрофилактика)
We have presented a comparative analysis of morbidity and mortality in the tick-borne encephalitis (TBE) in the south of the Russian Far East in the period 1980 - 2014. In the period from 2008 to 2014 using the enzyme-linked immunoassay (ELISA) was examined 10,599 copies ticks or leukocyte fraction of blood (n = 5561) of people who indicate to the fact of tick bites. Blood samples and ticks positive in ELISA additionally examined by PCR and virus isolation. Under diagnosis of TBE cases in the 1980s resulted in lower figures morbidity and mortality artificially excessive to 39% (average 28%). In the 1990s there was a sharp rise in the incidence of TBE (median 15.3% mortality). In the 2000s there was a trend to a decrease in the number of cases and deaths (average case fatality rate of 6.3 -10.5%). The incidence rate for 35-year follow-up period ranged from 0.85 to 9.88 per 100 thousand population, mortality was 14.8 ± 0.7%. The degree of danger of the epidemic on TBE synchronously reflected in the rate of antigen detection of TBE virus in humans and ticks attached themselves. In the year’s high morbidity and mortality (in 2009 and 2010) antigen detection in ticks and in human blood reached a maximum. Isolated from the blood of these patients three TBE virus strains indicated that only a complete virus capable of replicating determines the variety clinical forms of the infection.